2024
DOI: 10.1186/s12874-024-02218-1
|View full text |Cite
|
Sign up to set email alerts
|

Log odds of positive lymph nodes (LODDS)-based novel nomogram for survival estimation in patients with invasive micropapillary carcinoma of the breast

Xiangdi Meng,
Furong Hao,
Nan Wang
et al.

Abstract: Background Invasive micropapillary carcinoma (IMPC) of the breast is known for its high propensity for lymph node (LN) invasion. Inadequate LN dissection may compromise the precision of prognostic assessments. This study introduces a log odds of positive lymph nodes (LODDS) method to address this issue and develops a novel LODDS-based nomogram to provide accurate prognostic information. Methods The study analyzed data from 1,901 patients with breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Accurate evaluation of patients’ lymph node status holds considerable significance in managing and post-surgery monitoring of esophageal cancer. The LODDS staging system, known for its effective prognostic prediction in various cancers ( 15 , 20 , 21 ), is a relatively new approach to lymph node staging. However, research on its prognostic effectiveness for advanced esophageal squamous cell carcinoma is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate evaluation of patients’ lymph node status holds considerable significance in managing and post-surgery monitoring of esophageal cancer. The LODDS staging system, known for its effective prognostic prediction in various cancers ( 15 , 20 , 21 ), is a relatively new approach to lymph node staging. However, research on its prognostic effectiveness for advanced esophageal squamous cell carcinoma is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have found that the LODDS staging system may be more effective at prognostic prediction than the LNR staging system ( 28 , 31 ). Many people hold that the LODDS value can be utilized as a new prognostic index, and that it is more accurate than the existing relevant standards for various tumors ( 15 , 21 ). However, its accuracy in esophageal cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%